1986
DOI: 10.1118/1.595963
|View full text |Cite
|
Sign up to set email alerts
|

Penumbral measurements in water for high‐energy x rays

Abstract: Ionization chambers of varying inside diameter have been used to investigate the penumbral region of 60Co, 6-MV, and 31-MV x-ray beams. Measurements were made in water at varying depths up to 25 cm for a square field of side length 10 cm. The dependence of the penumbral widths on both the inside diameter of the ionization chamber and the depth in water is established along with the asymmetry of the penumbral distributions about the 50% level. A standard correction is indicated to eliminate the dependence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“…As shown by Dawson et al (24) , the 80% – 20% penumbra width measured with a 6‐mm diameter chamber would be 3 mm larger than the width measured with an infinitely narrow detector for 6‐MV photons. This observation is generally supported by the data in Fig.…”
Section: Resultsmentioning
confidence: 79%
“…As shown by Dawson et al (24) , the 80% – 20% penumbra width measured with a 6‐mm diameter chamber would be 3 mm larger than the width measured with an infinitely narrow detector for 6‐MV photons. This observation is generally supported by the data in Fig.…”
Section: Resultsmentioning
confidence: 79%
“…The reduction becomes more pronounced when profile data are collected in edge‐on orientation. Assuming a linear relationship with slope = 1 between detector size‐induced deviations in penumbra width and axial detector radius, r, 30 , 31 deviations over the profile penumbra are expected to be 0.5r or 0.3 mm for the diode detector in axial orientation. In edge‐on orientation, the effective detector cross‐section becomes rectangular in shape and over an order of magnitude smaller in width (i.e., 20 μm).…”
Section: Discussionmentioning
confidence: 99%
“…The use of microchambers (active volume = 10 -3 cm 3 ) is recommended [5,12] to minimize the broadening of the penumbra. Dawson et al reported that the dependence of the penumbral width on the detector size is independent of beam energy and depth in water [4] but is linear with detector size at a single depth. This linear relationship was used to correct penumbral width values with detector size [2].…”
Section: Introductionmentioning
confidence: 97%
“…The effect of the detector volume on measured penumbral width has been widely published in the literature [2][3][4][5][6][7][8][9] in terms of convoluting the real profile, due to volume averaging and electron transport alteration by the detector [10]. Recently, American Association of Physicists in Medicine [11] released a report recommending the use of small volume chambers for small fields B4 9 4 cm 2 [12].…”
Section: Introductionmentioning
confidence: 99%